The Application of Problem Posing Learning Model to Improve Physics Learning Outcomes on Sound Wave Material - Raiyan Maulina; Agus Wahyuni; A Halim (Asian Journal of Science Education, 2020)
This study aimed to find out how to apply the problem posing model to improve physics learning outcomes in class XI. This study used a descriptive statistical approach, and it was a gradual study. The stages used in this study were planning, implementing, observing, and reflecting. The subjects in this study were 30 students of class XI IA1 of SMAN 1 Lhoknga. The improvement shown in the average score obtained by students and and the classical limitations from cycle I to cycle III, namely 40%, 54%, 94% and 50%, 70%, 90%. Learning outcomes obtained by students can be improved by: students practice to understand the material conveyed by the teacher and students practice to respond the learning conveyed by the teacher.Keywords: Problem posing, learning, learning outcomes